Pelatihan dan Pendampingan Implementasi Online Assessment bagi Guru SMK Pariwisata Kertayasa Singakerta Ubud - Budiarta, I Komang; Sawitri, Ni Luh Putu Dian; Joni, Dewa Ayu Ari Wiryadi; Murtini, Ni Made Wersi; Devi, Ida Ayu Dwi Utari Pithaloka; Dewi, I Gusti Agung Pracita Julita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The latest assessment paradigm emphasizes that assessment is not only used for assessment but also for the learning process. It encourages teachers at SMK Pariwisata Kertayasa Singakerta Ubud to innovate in the assessment process, such as online assessments. The observation results showed that teachers needed training and mentoring on the online assessments. It underlies the implementation of the community service program carried out by the team of the English Language Education Study Program, FKIP Unmas Denpasar entitled “Training and Mentoring Online Assessment Implementation for SMK Pariwisata Kertayasa Singakerta Ubud Teachers.” After the observation, training and mentoring activities were then carried out on 2 and 15 July 2024. The training activities showed an increase in understanding of the participants regarding the implementation of online assessments, especially Quizizz, Kahoot and Formative. This can be seen from the pre-test and post-test results. The teachers also showed their enthusiasm and activeness. In the mentoring activity, the teachers were also able to implement online assessments well. They were able to use online assessments not only to create variations in assessments but also to make the assessment process more effective and efficient.